Manganese dioxide positive electrode material, positive electrode plate, preparation method of positive electrode plate and zinc ion battery
By using mixed materials of micron- and nano-sized manganese dioxide particles with water-based adhesives and conductive agents, a manganese dioxide positive electrode sheet for zinc-ion batteries was prepared, and the poor processing performance of water-based MnO2 positive electrode sheet in the prior art was solved. Problem, achieving better electrochemical performance and cost-effectiveness.
Patent Information
- Application Number
- CN202310944078.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the processability of using water-based adhesives to prepare MnO2 positive electrode sheets is very poor, especially the water-based MnO2 positive electrode.
A mixed material of micron-scale manganese dioxide particles and nano-scale manganese dioxide particles, combined with aqueous adhesives and conductive agents, was used to prepare a manganese dioxide positive electrode sheet for zinc ion batteries.
The processability and electrochemical performance of the water-based MnO2 positive electrode sheet are improved, while reducing the cost and environmental load of the positive electrode.
Smart Images

Figure CN119481028A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to aqueous zinc ion batteries, and in particular, the present invention relates to a manganese dioxide positive electrode material for a zinc ion battery, a method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, a manganese dioxide positive electrode sheet for a zinc ion battery, and a zinc ion battery. Background Art
[0002] Rechargeable zinc-ion battery is a rechargeable battery that uses manganese oxide material as positive electrode active material, zinc as negative electrode active material, and an aqueous solution containing zinc ions as electrolyte. This battery has the characteristics of being inexpensive.
[0003] Although zinc-ion batteries have attracted the attention of researchers and developers in the energy field due to their high safety and low cost, the cathode materials are mostly nanomaterials, and their high specific surface area requires the use of binders such as PVDF with NMP as the solvent (see Figure 1 ). The environmental load and cost of using NMP are very high, and PVDF is currently in short supply. Considering the cost, environmental load and binder resources, aqueous MnO2 cathode is a better choice than NMP-based MnO2 cathode.
[0004] However, the existing technology pays little attention to the processing performance of MnO2 positive electrodes, especially aqueous MnO2 positive electrodes. The reason is that nano-MnO2 powder is currently used to prepare positive electrode slurry, which has a large specific surface area and cannot be prepared using aqueous adhesives. As a result, the processing performance of MnO2 positive electrode sheets prepared using aqueous adhesives is very poor. Summary of the invention
[0005] The main purpose of the present invention is to provide a manganese dioxide positive electrode material for a zinc ion battery, a method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, a manganese dioxide positive electrode sheet for a zinc ion battery and a zinc ion battery, so as to solve the technical problem of poor processing performance of MnO2 positive electrode sheets prepared using water-based adhesives in the prior art.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a manganese dioxide positive electrode material for a zinc ion battery is provided, the manganese dioxide positive electrode material comprising: a mixed material of micron-sized manganese dioxide particles and nano-sized manganese dioxide particles, an aqueous binder, and a conductive agent; wherein the micron-sized manganese dioxide particles have an average particle size of 1-10 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-500 nm.
[0007] Furthermore, in the above-mentioned manganese dioxide positive electrode material for zinc ion batteries, the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is 99:1 to 60:40, preferably 90:10 to 60:40.
[0008] Furthermore, in the above-mentioned manganese dioxide positive electrode material for zinc ion battery, the aqueous binder is selected from the group consisting of: polyacrylonitrile, styrene-butadiene rubber, polyacrylic acid and any combination thereof.
[0009] Furthermore, in the above manganese dioxide positive electrode material for zinc ion battery, the micron-sized manganese dioxide particles have an average particle size of 1-5 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-200 nm.
[0010] Furthermore, in the above-mentioned manganese dioxide positive electrode material for zinc ion batteries, the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is 80:20 to 60:40.
[0011] According to another aspect of the present invention, a method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery is provided, the method comprising the following steps: step S1: mixing micron-sized manganese dioxide particles, nano-sized manganese dioxide particles, an aqueous binder and a conductive agent to form a manganese dioxide positive electrode material; step S2: adding water to the manganese dioxide positive electrode material to form a manganese dioxide positive electrode slurry; step S3: coating the manganese dioxide positive electrode slurry on a current collector to form a manganese dioxide positive electrode sheet; wherein the micron-sized manganese dioxide particles have an average particle size of 1-10 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-500 nm.
[0012] Furthermore, in the above method, the weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles is 99:1 to 60:40, preferably 90:10 to 60:40.
[0013] Furthermore, in the above method, the water-based adhesive is selected from the group consisting of polyacrylonitrile, styrene-butadiene rubber, polyacrylic acid and any combination thereof.
[0014] Further, in the above method, the micron-sized manganese dioxide particles have an average particle size of 1-5 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-200 nm.
[0015] Furthermore, in the above method, the weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles is 80:20 to 60:40.
[0016] According to another aspect of the present invention, a manganese dioxide positive electrode sheet for a zinc ion battery is provided. The manganese dioxide positive electrode sheet comprises the above-mentioned manganese dioxide positive electrode material or is prepared by the above-mentioned method.
[0017] According to another aspect of the present invention, a zinc ion battery is provided, comprising: a positive electrode sheet, a negative electrode sheet, and a separator, wherein the positive electrode sheet comprises the above-mentioned manganese dioxide positive electrode material or is prepared by the above-mentioned method.
[0018] According to the manganese dioxide positive electrode material for zinc ion battery, the method for preparing manganese dioxide positive electrode sheet for zinc ion battery, the manganese dioxide positive electrode sheet for zinc ion battery and the zinc ion battery of the present invention, by using a mixture of micron-sized manganese dioxide particles and nano-sized manganese dioxide particles with an average particle size in a specific range, the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheet are improved, while the cost and environmental load of the positive electrode are reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The NMP-based MnO2 positive electrode sheet prepared with PVDF binder has poor processability.
[0020] Figure 2 The positive electrode sheet prepared in Example 1 of the present application is shown, wherein the slurry is successfully prepared, the film is easy to draw, and the processability is good.
[0021] Figure 3 The slurry prepared in Comparative Example 3 is shown, in which the slurry preparation was unsuccessful, the film could not be drawn, and the processability was poor. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments. The following embodiments are merely exemplary and do not constitute a limitation on the scope of protection of the present invention.
[0023] As described in the background technology, in the prior art, nano MnO2 powder is generally used to prepare positive electrode slurry. However, due to the large specific surface area of nano MnO2 powder, it is impossible to prepare slurry using aqueous adhesives, resulting in poor processing performance of MnO2 positive electrode sheets prepared using aqueous adhesives. Therefore, further improvement is still needed. In view of the problems in the prior art, according to a typical embodiment of the present application, a manganese dioxide positive electrode material for a zinc ion battery is provided, the manganese dioxide positive electrode material comprising: a mixed material of micron-sized manganese dioxide particles and nano-sized manganese dioxide particles, an aqueous adhesive, and a conductive agent; wherein the micron-sized manganese dioxide particles have an average particle size of 1-10 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-500 nm.
[0024] Different from the prior art which uses only nano-MnO2 powder to prepare positive electrode slurry, in the manganese dioxide positive electrode material for zinc ion battery of the present application, a combination of micron-sized manganese dioxide particles with an average particle size of 1-10 μm and nano-sized manganese dioxide particles with an average particle size of 100-500 nm is used as the active positive electrode material to prepare the positive electrode slurry, which can reduce the specific surface area of the manganese dioxide particles, so that the positive electrode slurry can be prepared using an aqueous binder, thereby improving the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheet, while reducing the cost and environmental load of the positive electrode.
[0025] According to different embodiments, the micron-sized manganese dioxide particles may have an average particle size of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, or 10 μm. Specifically, the micron-sized manganese dioxide particles can have a size of 1 μm-10 μm, 1 μm-9.5 μm, 1 μm-9 μm, 1 μm-8.5 μm, 1 μm-8 μm, 1 μm-7.5 μm, 1 μm-7 μm, 1 μm-6.5 μm, 1 μm-6 μm, 1 μm-5.5 μm, 1 μm-4.5 μm, 1 μm-4 μm, 1.5 μm-10 μm, 1.5 μm-9.5 μm, 1.5 μm-9 μm, 1.5 μm-8.5 μm, 1.5 μm-8 μm, 1.5 μm-7.5 μm, 1.5 μm-7.5 μm, 1.5 μm-6.5 μm, 1.5 μm-6 μm, 1.5 μm-5.5 μm, 1.5 μm-4.5μm, 1.5μm-4μm, 2μm-10μm, 2μm-9.5μm, 2μm-9μm, 2μm-8.5μm, 2μm- 8μm, 2μm-7.5μm, 2μm-7μm, 2μm-6.5μm, 2μm-6μm, 2μm-5.5μm, 2μm-4.5μm, 2 μm-4μm, 3μm-10μm, 3μm-9.5μm, 3μm-9μm, 3μm-8.5μm, 3μm-8μm, 3μm-7.5μm m, 3 μm-7 μm, 3 μm-6.5 μm, 3 μm-6 μm, 3 μm-5.5 μm, 3 μm-4.5 μm or 3 μm-4 μm.
[0026] Similarly, for different embodiments, the nanometer-scale manganese dioxide particles can have an average particle size of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm. Specifically, the nanometer-scale manganese dioxide particles can have an average particle size of 100-500nm, 100-450nm, 100-400nm, 100-350nm, 100-300nm, 100-250nm, 100-200nm, 150-500nm, 150-450nm, 150-400nm, 150-350nm, 150-300nm, 150-250nm, 200-500nm, 200-450nm, 200-400nm, 200-350nm or 200-300nm.
[0027] Preferably, in the manganese dioxide positive electrode material for zinc ion batteries, the micron-sized manganese dioxide particles may have an average particle size of 1-5 μm, and the nano-sized manganese dioxide particles may have an average particle size of 100-200 nm.
[0028] In some embodiments of the present application, in the manganese dioxide positive electrode material for zinc ion batteries, the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is 99:1 to 60:40, preferably 90:10 to 60:40. When the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is within this range, the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheet can be significantly improved.
[0029] Specifically, for different embodiments, the weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles can be 99:1, 95:5, 90:10, 85:15, 80:20, 75:25, 70:30, 65:35 or 60:40. Specifically, the weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles can be 99:1-60:40, 99:1-65:35, 99:1-70:30, 99:1-75:25, 99:1-80:20, 95:5-60:40, 95:5-65:35, 95:5-70:30, 95:5-75:25, 95:5-80:20, 90:10-6 0:40, 90:10-65:35, 90:10-70:30, 90:10-75:25, 90:10-80:20, 85:15-60:40, 85:15-65:35, 85:15-70:30, 85:15-75:25, 80:20-60:40, 80:20-65:35, 80:20-70:30 or 80:20-75:25.
[0030] Preferably, in the manganese dioxide positive electrode material for zinc ion batteries, the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is 80:20 to 60:40. When the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is within this range, the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheet can be more significantly improved.
[0031] In some embodiments of the present application, in the manganese dioxide positive electrode material for zinc ion batteries, the conductive agent can be a combination of one or more of carbon black, VGCF, CNTs and graphene, etc. The above conductive agents are given only as examples and are not intended to be limiting. Those skilled in the art can select specific conductive agents as needed.
[0032] In some embodiments of the present application, in the manganese dioxide positive electrode material for zinc ion batteries, the aqueous binder is selected from the group consisting of: polyacrylonitrile, styrene-butadiene rubber, polyacrylic acid, and any combination thereof. The above aqueous binders are given only as examples and are not intended to be limiting. Those skilled in the art can select specific aqueous binders as needed. In the present application, the cost and environmental load of the positive electrode are reduced by using an aqueous binder.
[0033] According to another typical embodiment of the present invention, a method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery is provided, comprising the following steps: step S1: mixing micron-sized manganese dioxide particles, nano-sized manganese dioxide particles, an aqueous binder and a conductive agent to form a manganese dioxide positive electrode material; step S2: adding water to the manganese dioxide positive electrode material to form a manganese dioxide positive electrode slurry; step S3: coating the manganese dioxide positive electrode slurry on a current collector to form a manganese dioxide positive electrode sheet; wherein the micron-sized manganese dioxide particles have an average particle size of 1-10 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-500 nm.
[0034] Different from the prior art which uses only nano-MnO2 powder to prepare positive electrode sheets, in the method for preparing manganese dioxide positive electrode sheets for zinc ion batteries of the present application, a combination of micron-sized manganese dioxide particles with an average particle size of 1-10 μm and nano-sized manganese dioxide particles with an average particle size of 100-500 nm is used as the active positive electrode material to prepare the positive electrode sheets, which can reduce the specific surface area of the manganese dioxide particles, so that the positive electrode slurry can be prepared using an aqueous binder, thereby improving the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheets, while reducing the cost and environmental load of the positive electrode.
[0035] According to different embodiments, the micron-sized manganese dioxide particles may have an average particle size of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, or 10 μm. Specifically, the micron-sized manganese dioxide particles can have a size of 1 μm-10 μm, 1 μm-9.5 μm, 1 μm-9 μm, 1 μm-8.5 μm, 1 μm-8 μm, 1 μm-7.5 μm, 1 μm-7 μm, 1 μm-6.5 μm, 1 μm-6 μm, 1 μm-5.5 μm, 1 μm-4.5 μm, 1 μm-4 μm, 1.5 μm-10 μm, 1.5 μm-9.5 μm, 1.5 μm-9 μm, 1.5 μm-8.5 μm, 1.5 μm-8 μm, 1.5 μm-7.5 μm, 1.5 μm-7.5 μm, 1.5 μm-6.5 μm, 1.5 μm-6 μm, 1.5 μm-5.5 μm, 1.5 μm-4.5μm, 1.5μm-4μm, 2μm-10μm, 2μm-9.5μm, 2μm-9μm, 2μm-8.5μm, 2μm- 8μm, 2μm-7.5μm, 2μm-7μm, 2μm-6.5μm, 2μm-6μm, 2μm-5.5μm, 2μm-4.5μm, 2 μm-4μm, 3μm-10μm, 3μm-9.5μm, 3μm-9μm, 3μm-8.5μm, 3μm-8μm, 3μm-7.5μm m, 3 μm-7 μm, 3 μm-6.5 μm, 3 μm-6 μm, 3 μm-5.5 μm, 3 μm-4.5 μm or 3 μm-4 μm.
[0036] Similarly, for different embodiments, the nanometer-scale manganese dioxide particles can have an average particle size of 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm. Specifically, the nanometer-scale manganese dioxide particles can have an average particle size of 100-500nm, 100-450nm, 100-400nm, 100-350nm, 100-300nm, 100-250nm, 100-200nm, 150-500nm, 150-450nm, 150-400nm, 150-350nm, 150-300nm, 150-250nm, 200-500nm, 200-450nm, 200-400nm, 200-350nm or 200-300nm.
[0037] Preferably, in the manganese dioxide positive electrode material for zinc ion batteries, the micron-sized manganese dioxide particles may have an average particle size of 1-5 μm, and the nano-sized manganese dioxide particles may have an average particle size of 100-200 nm.
[0038] In some embodiments of the present application, in the method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is 99:1 to 60:40, preferably 90:10 to 60:40. When the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is within this range, the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheet can be significantly improved.
[0039] Specifically, for different embodiments, the weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles can be 99:1, 95:5, 90:10, 85:15, 80:20, 75:25, 70:30, 65:35 or 60:40. Specifically, the weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles can be 99:1-60:40, 99:1-65:35, 99:1-70:30, 99:1-75:25, 99:1-80:20, 95:5-60:40, 95:5-65:35, 95:5-70:30, 95:5-75:25, 95:5-80:20, 90:10-6 0:40, 90:10-65:35, 90:10-70:30, 90:10-75:25, 90:10-80:20, 85:15-60:40, 85:15-65:35, 85:15-70:30, 85:15-75:25, 80:20-60:40, 80:20-65:35, 80:20-70:30 or 80:20-75:25.
[0040] Preferably, in the method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is 80:20 to 60:40. When the weight ratio of micron-sized manganese dioxide particles to nano-sized manganese dioxide particles is within this range, the processing performance and electrochemical performance of the aqueous MnO2 positive electrode sheet can be more significantly improved.
[0041] In some embodiments of the present application, in the method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, the conductive agent may be a combination of one or more of carbon black, VGCF, CNTs, and graphene, etc. The above conductive agents are given only as examples and are not intended to be limiting. Those skilled in the art may select a specific conductive agent as needed.
[0042] In some embodiments of the present application, in the method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, the aqueous binder is selected from the group consisting of: polyacrylonitrile, styrene-butadiene rubber, polyacrylic acid, and any combination thereof. The above aqueous binders are given only as examples and are not intended to be limiting. Those skilled in the art can select specific aqueous binders as needed. In the present application, the cost and environmental load of the positive electrode are reduced by using an aqueous binder.
[0043] In some embodiments of the present application, in the method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, in step S2, the water may be deionized water, but is not limited thereto.
[0044] In some embodiments of the present application, in the method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, in step S3, the current collector includes but is not limited to stainless steel foil, titanium foil, stainless steel mesh, titanium mesh, carbon-coated stainless steel foil, carbon-coated titanium foil, carbon paper, carbon cloth, etc. Those skilled in the art can select a suitable current collector as needed.
[0045] According to another typical embodiment of the present invention, there is provided a manganese dioxide positive electrode sheet for a zinc ion battery, the manganese dioxide positive electrode sheet comprising the manganese dioxide positive electrode material of the present invention or prepared by the method of the present invention. By comprising the manganese dioxide positive electrode material of the present invention or preparing by the method of the present invention, the manganese dioxide positive electrode sheet for a zinc ion battery can be easily prepared, the electrochemical performance is improved, and the preparation cost and environmental load of the positive electrode are reduced.
[0046] According to another typical embodiment of the present invention, a zinc ion battery is provided, comprising: a positive electrode sheet, a negative electrode sheet, and a separator, wherein the positive electrode sheet comprises the manganese dioxide positive electrode material of the present invention or is prepared by the method of the present invention. Since the positive electrode sheet comprises the manganese dioxide positive electrode material of the present invention or is prepared by the method of the present invention, the zinc ion battery can be easily prepared, the electrochemical performance is improved, and the preparation cost and environmental load are reduced.
[0047] Example
[0048] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0049] Preparation of batteries
[0050] Example 1 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 90:10)
[0051] Take 6.3g of micron-sized manganese dioxide (D50 = 5μm) particles and 0.7g of nano-sized manganese dioxide (D50 = 200nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of 20μm thick stainless steel foil and dry it at 60℃ for 20min to make a positive electrode. The positive electrode is combined with a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) to form a CR2032 button battery.
[0052] Example 2 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 80:20)
[0053] Take 5.6g of micron-sized manganese dioxide (D50 = 5μm) particles and 1.4g of nano-sized manganese dioxide (D50 = 200nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode, a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) form a CR2032 button battery.
[0054] Example 3 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 60:40)
[0055] Take 4.2g of micron-sized manganese dioxide (D50 = 5μm) particles and 2.8g of nano-sized manganese dioxide (D50 = 200nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of 20μm thick stainless steel foil and dry it at 60℃ for 20min to make a positive electrode. The positive electrode is combined with a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) to form a CR2032 button battery.
[0056] Comparative Example 1 (micron-sized manganese dioxide only)
[0057] Take 7g of micron-sized manganese dioxide (D50 = 5μm) particles, mix the manganese dioxide particles with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of 20μm thick stainless steel foil and dry it at 60℃ for 20min to make a positive electrode. The positive electrode, 150μm thick zinc sheet (negative electrode), glass fiber separator, 150μL aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) are combined into a CR2032 button battery.
[0058] Comparative Example 2 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 50:50)
[0059] Take 3.5g of micron-sized manganese dioxide (D50=5μm) particles and 3.5g of nano-sized manganese dioxide (D50=200nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. The slurry is coated on the surface of a 20μm thick stainless steel foil, but the slurry is unstable, dries very quickly, and is not easy to draw a film.
[0060] Comparative Example 3 (nano-manganese dioxide only)
[0061] 7g of nano-sized manganese dioxide (D50 = 200nm) particles were taken, the manganese dioxide particles were mixed with LA132 binder and SuperP carbon black conductive agent in a weight ratio of 7:1:2, and deionized water was added to prepare a slurry with a solid content of 40.0wt.%. Figure 3 As shown, the slurry preparation was unsuccessful and the film could not be drawn.
[0062] Example 4 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 90:10)
[0063] Take 6.3g of micron-sized manganese dioxide (D50 = 1μm) particles and 0.7g of nano-sized manganese dioxide (D50 = 100nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode, a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) form a CR2032 button battery.
[0064] Example 5 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 80:20)
[0065] Take 5.6g of micron-sized manganese dioxide (D50 = 1μm) particles and 1.4g of nano-sized manganese dioxide (D50 = 100nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode, a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) form a CR2032 button battery.
[0066] Example 6 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 60:40)
[0067] Take 4.2g of micron-sized manganese dioxide (D50 = 1μm) particles and 2.8g of nano-sized manganese dioxide (D50 = 100nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode, a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) form a CR2032 button battery.
[0068] Comparative Example 4 (micron-sized manganese dioxide only)
[0069] Take 7g of micron-sized manganese dioxide (D50 = 1μm) particles, mix the manganese dioxide particles with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of 20μm thick stainless steel foil and dry it at 60℃ for 20min to make a positive electrode. The positive electrode, 150μm thick zinc sheet (negative electrode), glass fiber separator, and 150μL aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) are combined into a CR2032 button battery.
[0070] Comparative Example 5 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 50:50)
[0071] 3.5g of micron-sized manganese dioxide (D50=1μm) particles and 3.5g of nano-sized manganese dioxide (D50=100nm) particles were taken, and the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) were mixed with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and deionized water was added to prepare a slurry with a solid content of 40.0wt.%. However, the slurry preparation was unsuccessful and the film could not be drawn.
[0072] Comparative Example 6 (nano-manganese dioxide only)
[0073] 7g of nano-sized manganese dioxide (D50=100nm) particles were taken, mixed with LA132 binder and SuperP carbon black conductive agent in a weight ratio of 7:1:2, and deionized water was added to prepare a slurry with a solid content of 40.0wt.%. However, the slurry preparation was unsuccessful and no film could be drawn.
[0074] Example 7 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 90:10)
[0075] Take 6.3g of micron-sized manganese dioxide (D50 = 10μm) particles and 0.7g of nano-sized manganese dioxide (D50 = 500nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode, a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) form a CR2032 button battery.
[0076] Example 8 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 80:20)
[0077] Take 5.6g of micron-sized manganese dioxide (D50 = 10μm) particles and 1.4g of nano-sized manganese dioxide (D50 = 500nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode is combined with a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) to form a CR2032 button battery.
[0078] Example 9 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 60:40)
[0079] Take 4.2g of micron-sized manganese dioxide (D50 = 10μm) particles and 2.8g of nano-sized manganese dioxide (D50 = 500nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of a 20μm thick stainless steel foil and dry it at 60°C for 20min to make a positive electrode. The positive electrode, a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) form a CR2032 button battery.
[0080] Comparative Example 7 (micron-sized manganese dioxide only)
[0081] Take 7g of micron-sized manganese dioxide (D50 = 10μm) particles, mix the manganese dioxide particles with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of 20μm thick stainless steel foil and dry it at 60℃ for 20min to make a positive electrode. The positive electrode, 150μm thick zinc sheet (negative electrode), glass fiber separator, 150μL aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) are combined into a CR2032 button battery.
[0082] Comparative Example 8 (the weight ratio of micron-sized manganese dioxide to nano-sized manganese dioxide is 50:50)
[0083] Take 3.5g of micron-sized manganese dioxide (D50 = 10μm) particles and 3.5g of nano-sized manganese dioxide (D50 = 500nm) particles, mix the manganese dioxide particles (micron-sized manganese dioxide + nano-sized manganese dioxide) with LA132 binder and Super P carbon black conductive agent in a weight ratio of 7:1:2, and add deionized water to make a slurry with a solid content of 40.0wt.%. Apply the slurry on the surface of 20μm thick stainless steel foil and dry it at 60℃ for 20min to make a positive electrode. The positive electrode is combined with a 150μm thick zinc sheet (negative electrode), a glass fiber separator, and 150μL of an aqueous electrolyte (zinc sulfate aqueous solution, concentration 2M) to form a CR2032 button battery.
[0084] Comparative Example 9 (nano-manganese dioxide only)
[0085] 7g of nano-sized manganese dioxide (D50=500nm) particles were taken, mixed with LA132 binder and SuperP carbon black conductive agent in a weight ratio of 7:1:2, and deionized water was added to prepare a slurry with a solid content of 40.0wt.%. However, the slurry preparation was unsuccessful and no film could be drawn.
[0086] Battery performance test
[0087] 1. Determination of capacity retention rate
[0088] The discharge capacity and cycle performance of the battery are tested using a charge and discharge instrument.
[0089] First, charge at an ambient temperature of 23°C, a charging voltage of 1.8V, and a charging current of 100mA / g, and then discharge at a discharge current of 100mA / g and a termination voltage of 0.8V, and measure the first discharge capacity (discharge capacity of the 1st cycle). Next, charge and discharge are repeated at an ambient temperature of 23°C, a charging voltage of 1.8V, a charging current of 100mA / g, and a discharge current of 50mA / g and a termination voltage of 0.8V. Subsequently, the discharge capacity of the 50th cycle is measured. Next, the capacity retention rate (%) after 50 cycles is calculated based on the following formula using the discharge capacity of the 1st cycle and the discharge capacity of the 50th cycle.
[0090] Capacity retention rate after 50 cycles [%] = (discharge capacity after 50th cycle / first discharge capacity (first cycle)) × 100%.
[0091] 2. Determination of peel strength
[0092] Sample preparation: Use scissors to cut a certain length (at least 15cm) of double-sided tape (width 2cm) and stick it on the positive electrode. Use a roller to flatten the surface of the tape, and then use a cutter to cut the sample along the edge of the tape. Tear off the white part of the double-sided tape, and use the double-sided tape to stick the electrode to a steel plate wiped clean with alcohol, with the current collector facing up, and then use a roller to roll back and forth on the current collector 10 times.
[0093] Test: Separate the current collector and the pole piece of half the length of the sample, and clamp the steel plate and the separated current collector to the universal testing machine at 180 degrees. The separated current collector is clamped in the upper fixture, and the steel plate is clamped in the lower fixture. The upper fixture of the universal testing machine is loaded with a certain force and slowly moved upward to the end point, so that the other half of the current collector and the pole piece that are not separated are also peeled off. The universal testing machine automatically calculates the peeling strength through the measured force that causes the other half of the current collector and the pole piece to peel off and the width of the pole piece sample.
[0094] Peel strength (mN / mm) = peel force (mN) / sample width (mm)
[0095] Table 1 shows the evaluation results of the zinc ion batteries prepared according to Comparative Examples 1-3 and Examples 1-3.
[0096] Table 1
[0097]
[0098] Table 2 shows the evaluation results of the zinc ion batteries prepared according to Comparative Examples 4-6 and Examples 4-6.
[0099] Table 2
[0100]
[0101]
[0102] Table 3 shows the evaluation results of the zinc ion batteries prepared according to Comparative Examples 7-9 and Examples 7-9.
[0103] Table 3
[0104]
[0105] By comparing the embodiments of the present invention with the comparative examples, it can be seen from the above experimental results that the above embodiments of the present invention achieve the following technical effects:
[0106] - Compared with Comparative Examples 3, 6 and 9 containing only nano-sized manganese dioxide particles, Examples 1-9 of the present invention using a mixture of micron-sized manganese dioxide particles and nano-sized manganese dioxide particles having an average particle size within a specific range improve the peel strength (processing performance) and electrochemical performance of the aqueous MnO2 positive electrode sheet, while reducing the cost and environmental load of the positive electrode;
[0107] -Compared with Comparative Examples 1, 4 and 7 containing only micron-sized manganese dioxide particles, Examples 1-9 of the present invention improve the electrochemical performance of aqueous MnO2 positive electrode sheets. Although Examples 1-9 are slightly reduced in peel strength, the peel strength achieved by Examples 1-9 is still within the acceptable and preferred range in the art.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A manganese dioxide positive electrode material for a zinc ion battery, characterized in that: The manganese dioxide positive electrode material comprises: - A mixed material of micron-sized manganese dioxide particles and nano-sized manganese dioxide particles, - water-based adhesives, and - conductive agent; The micron-sized manganese dioxide particles have an average particle size of 1-10 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-500 nm.
2. The manganese dioxide positive electrode material according to claim 1, characterized in that The weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles is 99:1 to 60:40, preferably 90:10 to 60:
40.
3. The manganese dioxide positive electrode material according to claim 1 or 2, characterized in that: The water-based adhesive is selected from the group consisting of polyacrylonitrile, styrene-butadiene rubber, polyacrylic acid and any combination thereof.
4. The manganese dioxide positive electrode material according to claim 1 or 2, characterized in that: The micron-sized manganese dioxide particles have an average particle size of 1-5 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-200 nm.
5. The manganese dioxide positive electrode material according to claim 1 or 2, characterized in that: The weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles is 80:20 to 60:
40.
6. A method for preparing a manganese dioxide positive electrode sheet for a zinc ion battery, characterized in that: The following steps are involved: - Step S1: mixing micron-sized manganese dioxide particles, nano-sized manganese dioxide particles, an aqueous binder and a conductive agent to form a manganese dioxide positive electrode material; - Step S2: adding water to the manganese dioxide positive electrode material to form a manganese dioxide positive electrode slurry; - Step S3: coating the manganese dioxide positive electrode slurry on a current collector to form a manganese dioxide positive electrode sheet; The micron-sized manganese dioxide particles have an average particle size of 1-10 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-500 nm.
7. The method according to claim 6, characterized in that The weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles is 99:1 to 60:40, preferably 90:10 to 60:
40.
8. The method according to claim 6 or 7, characterized in that: The water-based adhesive is selected from the group consisting of polyacrylonitrile, styrene-butadiene rubber, polyacrylic acid and any combination thereof.
9. The method according to claim 6 or 7, characterized in that: The micron-sized manganese dioxide particles have an average particle size of 1-5 μm, and the nano-sized manganese dioxide particles have an average particle size of 100-200 nm.
10. The method according to claim 6 or 7, characterized in that: The weight ratio of the micron-sized manganese dioxide particles to the nano-sized manganese dioxide particles is 80:20 to 60:
40.
11. A manganese dioxide positive electrode sheet for a zinc ion battery, characterized in that: The manganese dioxide positive electrode material comprises the manganese dioxide positive electrode material according to any one of claims 1 to 5 or is prepared by the method according to any one of claims 6 to 10.
12. A zinc ion battery comprising: Positive electrode, The negative electrode, and Diaphragm, It is characterized in that The positive electrode sheet comprises the manganese dioxide positive electrode material according to any one of claims 1 to 5 or is prepared by the method according to any one of claims 6 to 10.